Red clay improver and red clay improvement method

Through rice husk ash and calcium carbide slag modification agent, gelling substances are formed to fill red clay, which solves the problem of reducing the strength of red clay, improves the compressive strength and stability of red clay, achieves economic and environmentally friendly improvement effects, and promotes the Utilization of industrial solid waste.

CN119320640APending Publication Date: 2025-01-17SHANDONG LUQIAO GROUP CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411441877.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The intensity of red clay is reduced under high temperature and rainfall conditions, resulting in engineering problems such as building foundation sinking and roadbed cracking. The existing improvement methods are costly or harmful to the environment.

Method used

Rice husk ash and industrial solid waste calcium carbide slag are used as red clay modification agents. By mixing and in the curing process, hydrated calcium silicate and calcium aluminate gel substances are formed, filling soil pores and ion exchange, thereby increasing red The compressive strength, shear strength and compression properties of clay.

Benefits of technology

It significantly improves the strength and stability of red clay, reduces soil expansion and shrinkage, solves the problem of roadbed treatment in red clay areas, and realizes the comprehensive utilization and environmental protection of industrial solid waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320640A_ABST
    Figure CN119320640A_ABST
Patent Text Reader

Abstract

The invention discloses a red clay improver and a red clay improvement method. The red clay modifier comprises rice hull ash and carbide slag. The improvement method of the red clay comprises the step of mixing the rice hull ash and the carbide slag with different mixing amounts with the red clay according to the optimal proportion. Obtaining the maximum dry density and the optimal water content of the mixed improved soil of each mixing amount; according to the maximum dry density and the optimal water content, the improved soil is prepared into multiple test pieces, and curing is conducted for 28 days; carrying out related mechanical property tests on the test pieces; and determining the optimal mixing amount of the rice hull ash and carbide slag improved red clay according to the mechanical property test result. According to the method, the unconfined compressive strength, the shear strength and the compression performance of the red clay can be remarkably improved, the improved materials are all industrial solid waste materials, the materials are convenient to obtain and low in cost, environmental pollution can be reduced, and the method is particularly suitable for solving the practical engineering problem in the red clay area.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of soil improvement, in particular to a red clay improver and a red clay improvement method. Background Art

[0002] Red clay is a reddish-brown clay formed by chemical weathering of carbonate rocks under mild and humid climatic conditions. It is widely distributed in southwestern China, such as Guangxi, Yunnan, and Guizhou, with typical regional differences. The mineral components of red clay mainly include kaolinite, montmorillonite, illite, etc. The special mineral composition and the climatic environment in which it is located create the characteristics of red clay such as high liquid limit, poor permeability and high porosity. When in the rainy season with high temperature and frequent rainfall, the strength of red clay decreases significantly after it comes into contact with water, and the soil is prone to shrinkage and cracking. In severe cases, the reduction in the bearing capacity of red clay often causes engineering problems such as sinking of building foundations, cracking of roadbeds, and instability of slopes.

[0003] At present, physical improvement, waste soil replacement and chemical improvement are commonly used methods for improving soil. Among them, physical improvement and waste soil replacement have not been widely used due to their high costs. Some chemical improvement methods, such as adding lime, cement and fly ash, not only consume a lot of raw materials and cause resource loss, but also have a great negative impact on the environment.

[0004] Therefore, there is an urgent need to develop a red clay improvement method with good improvement effect, economy and environmental protection in this field. Summary of the invention

[0005] The object of the present invention is to provide a red clay modifier and a red clay improvement method, wherein the red clay modifier can improve the unconfined compressive strength, shear strength index and compression performance of red clay, and the red clay modifier is mainly composed of rice husk ash, a byproduct of biomass power generation, and industrial solid waste carbide slag, with wide sources and low costs. The red clay modifier can not only improve the comprehensive utilization of industrial solid waste, but also improve red clay diseases, solve the problems of roadbed treatment in red clay areas, and achieve the purpose of "treating waste with waste".

[0006] To achieve the above object, the present invention provides the following technical solution: a red clay modifier, comprising the following components in parts by weight:

[0007] 5–23 parts of rice husk ash and 3–13 parts of carbide slag.

[0008] Preferably, the following components are included in parts by mass: 5 parts of rice husk ash and 3 parts of carbide slag.

[0009] Preferably, the following components are included in parts by mass: 10 parts of rice husk ash and 6 parts of carbide slag.

[0010] Preferably, the following components are included in parts by mass: 16 parts of rice husk ash and 9 parts of carbide slag.

[0011] Preferably, the following components are included in parts by mass: 23 parts of rice husk ash and 13 parts of carbide slag.

[0012] When a mixture of rice husk ash and carbide slag is added to red clay, the red clay particles will adhere to its surface, achieving a good filling effect. Filling rice husk ash and carbide slag into red clay will change its microstructure, and then change its physical properties, improving the strength and compression properties of red clay. At the same time, during the curing period, the two undergo hydration reactions to generate hydrated calcium silicate and hydrated calcium aluminate. Hydrated calcium silicate and hydrated calcium aluminate are insoluble in water and are ideal cementitious materials. Silicate gel will bond and cover the red clay particles and fill the pores in the soil. These gelling materials gradually change from a gel state to a crystalline state, and the red clay particles are gradually bonded. As the curing age increases, this gel gradually crystallizes into calcium silicate hydrates, and the microcrystals can be mechanically interlocked. With the assistance of water, carbide slag can dissociate into Ca 2+ and OH - . Na on the surface of red clay particles + and K + By ion exchange with Ca 2+ In addition, the alkaline environment will accelerate ion exchange. Since carbide slag is an alkaline substance, it can strengthen the Na + , K + With Ca 2+ Ion exchange between them. In this state, if Ca(OH)2 is still in a supersaturated state, Ca(OH)2 will react with the active SiO2 and Al2O3 in the soil to form hydrated calcium silicate and hydrated calcium aluminate. At the same time, some Ca(OH)2 can absorb CO2 in the air and water for carbonation. Hydrated calcium silicate, hydrated calcium aluminate and CaCO3 gradually harden to form crystalline compounds that are insoluble in water. In this process, fine soil particles agglomerate, cement and harden, and a dense overall structure is formed from the aggregate structure, thereby greatly improving the strength and water stability of the red clay soil and significantly reducing the expansion and contraction of the soil.

[0013] A method for improving a red clay modifier comprises the following steps:

[0014] Step 1: Mix different amounts of rice husk ash and carbide slag with red clay according to the optimal ratio of 65:35 to obtain improved soils of different amounts;

[0015] Step 2: Obtain the maximum dry density and optimum moisture content of the improved soil at each dosage after mixing;

[0016] Step 3: preparing various test specimens of each improved soil according to the maximum dry density and the optimum moisture content and curing them for 28 days;

[0017] Step 4: Conduct relevant mechanical property tests on each of the test specimens;

[0018] Step 5: According to the mechanical properties test results, determine the optimal dosage of rice husk ash and carbide slag to improve red clay.

[0019] Preferably, before step 1, the method further comprises crushing the red clay, and the red clay is crushed to a particle size of less than 2 mm.

[0020] Preferably, in step 2, obtaining the maximum dry density and optimum moisture content of the improved soil at each dosage after mixing comprises:

[0021] Divide the mixed materials of each dosage obtained by mixing into a plurality of samples;

[0022] Each dosage should be mixed with water according to at least 5 moisture contents;

[0023] The mixed samples were placed in plastic bags and sealed for 12 hours; the sealed samples were placed in a compaction cylinder and compacted;

[0024] Use a bulldozer to push out the sample in the cylinder, and take a representative soil sample from the center of the sample to measure its moisture content;

[0025] Draw the relationship curve between dry density and moisture content and obtain the maximum dry density and optimal moisture content of the sample.

[0026] Preferably, in step 3, the test specimen is prepared by a heavy test method and a small cylinder three-layer method; during the preparation process, each layer is about 800-900g, and after the small test cylinder is compacted, the sample should not be higher than 5mm from the top surface of the cylinder; the heavy test method is used and the preparation is carried out according to the small cylinder three-layer method, which specifically includes:

[0027] Each dosage should be mixed with water according to at least 5 moisture contents; each mixed sample should be placed in a plastic bag and sealed for 12 hours; each sealed sample should be placed in a small test tube and compacted; and the sample in the tube should be pushed out with a bulldozer.

[0028] Preferably, in the step four, the relevant mechanical property tests include: unconfined compressive strength, shear strength index and compression performance; the shear strength index is obtained by a triaxial test without consolidation and drainage; the unconfined compressive strength test specimens and the triaxial test specimens without consolidation and drainage are made by compaction method, and the specimen size is 39.1 mm in diameter × 80 mm in height, and is cured for 28 days under standard curing conditions, temperature of 20–22°C, and relative humidity of more than 95%; the compression performance is obtained by a consolidation test; the consolidation test is made by compression method, and the specimen size is 61.8 mm in diameter × 20 mm in height, and is cured for 28 days under standard curing conditions, temperature of 20–22°C, and relative humidity of more than 95%.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The red clay improvement method of the present invention can improve the red clay at the macro level, improve the high porosity, unconfined compressive strength and shear strength of the red clay, improve the compression performance and strength of the red clay, and thus improve the stability of the red clay roadbed;

[0031] (2) The red clay modifier of the present invention can react with red clay particles at the microscopic level to generate gel to fill the soil pores, while performing ion exchange to reduce the thickness of the water film on the surface of the red clay particles. The clay particles are cemented and hardened to form a dense overall structure, thereby greatly improving the strength of the red clay soil;

[0032] (3) The raw materials of the red clay improver used in the red clay improvement method of the present invention are all industrial solid waste, which is easy to obtain and has low cost. It not only reduces environmental pollution, but also solves practical engineering problems in red clay areas, and has outstanding economic and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a schematic diagram of the process of the red clay improvement test method in an embodiment of the present invention;

[0034] Figure 2 This is a photograph of the internal microstructure of the improved red clay prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0036] Please see attached Figure 1-2 The present invention provides a red clay modifier, comprising the following components in parts by weight:

[0037] 5–23 parts of rice husk ash and 3–13 parts of carbide slag.

[0038] A method for improving a red clay modifier comprises the following steps:

[0039] Step 1: crush the red clay to a particle size of less than 2 mm, and mix different amounts of rice husk ash and carbide slag with the red clay according to the optimal ratio to obtain improved soil of different amounts;

[0040] Step 2: Obtain the maximum dry density and optimum moisture content of the improved soil at each dosage after mixing; Obtaining the maximum dry density and optimum moisture content of the improved soil at each dosage after mixing includes:

[0041] Divide the mixed materials of each dosage obtained by mixing into a plurality of samples;

[0042] Each dosage should be mixed with water according to at least 5 moisture contents;

[0043] The mixed samples were placed in plastic bags and sealed for 12 hours; the sealed samples were placed in a compaction cylinder and compacted;

[0044] Use a bulldozer to push out the sample in the cylinder, and take a representative soil sample from the center of the sample to measure its moisture content;

[0045] Draw the relationship curve between dry density and moisture content and obtain the maximum dry density and optimal moisture content of the sample;

[0046] Step 3: Prepare various test specimens of each improved soil according to the maximum dry density and the optimum moisture content and perform 28-day curing; adopt a heavy test method and prepare the test specimens according to the small tube three-layer method; during the preparation process, each layer is about 800-900g, and after the small test tube is compacted, the sample should not be higher than the top surface of the tube by 5mm; adopt a heavy test method and prepare according to the small tube three-layer method specifically including:

[0047] Each dosage should be mixed with water according to at least 5 moisture contents; each mixed sample should be placed in a plastic bag and sealed for 12 hours; each sealed sample should be placed in a small test tube and compacted; and the sample in the tube should be pushed out with a bulldozer;

[0048] Step 4: Conduct relevant mechanical property tests on each of the test specimens; the relevant mechanical property tests include: unconfined compressive strength, shear strength index and compression performance; the shear strength index is obtained through an unconsolidated and undrained triaxial test; the unconfined compressive strength test specimens and the unconsolidated and undrained triaxial test specimens are made by compaction method, the specimen size is 39.1mm in diameter × 80mm in height, and are cured for 28 days under standard curing conditions and temperature of 20–22°C and relative humidity of more than 95%; the compression performance is obtained through consolidation test; the consolidation test is made by compression method, the specimen size is 61.8mm in diameter × 20mm in height, and is cured for 28 days under standard curing conditions and temperature of 20–22°C and relative humidity of more than 95%;

[0049] Step 5: According to the mechanical properties test results, determine the optimal dosage of rice husk ash and carbide slag to improve red clay.

[0050] The raw materials and components used in the examples of the present invention were purchased through commercial channels.

[0051] The red clay used in the present invention was taken from Yulin City, dried in the sun, passed through a 2 mm sieve and its basic physical properties were measured (see Table 1).

[0052] Table 1 Basic physical and mechanical properties of red clay

[0053]

[0054] The rice husk ash used in the present invention is a black loose amorphous powder obtained by burning rice husks at 600-800°C. The main component of the powder is SiO2 and the powder has high volcanic ash activity.

[0055] The carbide slag used in the present invention is off-white loose amorphous powder, which is a by-product in the process of producing acetylene. Its main component is Ca(OH)2 and it is strongly alkaline.

[0056] Embodiment 1:

[0057] Step 1. Mix rice husk ash and carbide slag in a ratio of 65:35.

[0058] Step 2: Take 110 g of rice husk ash and carbide slag mixture and 2090 g of red clay, prepare at least 5 samples, add different amounts of water (increasing by 2%-3% moisture content), mix evenly according to 5% mixture dosage, put into plastic bags and seal overnight for use.

[0059] Step 3: Use the heavy test method and prepare the compacted specimen according to the small cylinder three-layer method. During the preparation process, each layer is about 800-900g. After the small test cylinder is compacted, the sample should not be higher than 5mm above the top surface of the cylinder.

[0060] Step 4: Use a bulldozer to push the sample out of the cylinder, take a representative soil sample from the center of the sample and measure its moisture content. Draw a curve of the relationship between dry density and moisture content and obtain the maximum dry density and optimal moisture content of the sample.

[0061] Step 5: Take 150 g of rice husk ash and carbide slag mixture and 2850 g of red clay, mix them evenly according to 5% of the mixture, and prepare 15 samples with maximum dry density and optimal moisture content. The sample size is (diameter×height) 39.1 mm×80 mm.

[0062] Step 6: Take 40g of rice husk ash and carbide slag mixture and 760g of red clay, mix them evenly according to 5% of the mixture, prepare 3 samples with maximum dry density and optimal moisture content, and the sample size is (diameter×height) 61.8mm×20mm.

[0063] Step 7: Cure the two sizes of samples for 28 days at a temperature of 20-22°C and a relative humidity of more than 95%.

[0064] Step 8. According to the "Highway Geotechnical Test Code" (JTG-3430-2020), three parallel tests were carried out on the 5% modified red clay, and the average value was taken as the unconfined compressive strength of this group of samples.

[0065] Step 9. According to the Highway Geotechnical Test Code (JTG-3430-2020), the confining pressures are selected as 50 kPa, 100 kPa, 200 kPa and 300 kPa. Three parallel tests are carried out on 5% modified red clay to determine its shear strength index, cohesion and internal friction angle.

[0066] Step 10. According to the Highway Geotechnical Test Code (JTG-3430-2020), the consolidation pressure is selected as 50 kPa, 100 kPa, 200 kPa and 400 kPa. Three parallel tests are carried out on 5% modified red clay, and its compression modulus and compression coefficient are calculated according to the ep curve.

[0067] Embodiment 2:

[0068] The difference from Example 1 is that: 10% of the rice husk ash and carbide slag mixture is mixed evenly with red clay, wherein in step 2, 220g of the rice husk ash and carbide slag mixture and 1980g of red clay are taken; in step 5, 300g of the rice husk ash and carbide slag mixture and 2700g of red clay are taken; in step 6, 80g of the rice husk ash and carbide slag mixture and 720g of red clay are taken.

[0069] Embodiment 3:

[0070] The difference from Example 1 is that: 15% of the rice husk ash and carbide slag mixture is mixed evenly with red clay, wherein in step 2, 330g of the rice husk ash and carbide slag mixture and 1870g of red clay are taken; in step 5, 450g of the rice husk ash and carbide slag mixture and 2550g of red clay are taken; in step 6, 120g of the rice husk ash and carbide slag mixture and 680g of red clay are taken.

[0071] Embodiment 4:

[0072] The difference from Example 1 is that: 20% of the rice husk ash and carbide slag mixture is mixed evenly with red clay, wherein in step 2, 440g of the rice husk ash and carbide slag mixture and 1760g of red clay are taken; in step 5, 600g of the rice husk ash and carbide slag mixture and 2400g of red clay are taken; in step 6, 160g of the rice husk ash and carbide slag mixture and 640g of red clay are taken.

[0073] Example 5 (blank test):

[0074] The difference from Example 1 is that: no rice husk ash and carbide slag mixture is added, wherein 2200g of red clay is taken in step 2; 3000g of red clay is taken in step 5; and 800g of red clay is taken in step 6.

[0075] Referring to the national standard "Highway Geotechnical Test Code" (JTG3430-2020), the test results of unconfined compressive strength, cohesion, internal friction angle, compression modulus, and compression coefficient of Examples 1-5 are shown in Table 2 below.

[0076] Table 2 Test results of various embodiments

[0077]

[0078]

[0079] Compared with Example 5, after adding rice husk ash and carbide slag as red clay modifiers and curing for 28 days, it can be seen from Table 2 that the unconfined compressive strength, cohesion, internal friction angle and compression modulus of Examples 1-4 are improved to varying degrees, and the compression coefficient is significantly reduced. In Example 3, the unconfined compressive strength and cohesion reach peak values, which are 2.76 times and 3.01 times that of Example 5, respectively; in Example 4, the internal friction angle and compression modulus reach peak values, which are 2.72 times and 1.67 times that of Example 5, respectively, and the compression coefficient reaches the minimum value, which is about 39.29% lower than that of Example 5.

[0080] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A red clay modifier, characterized in that: It includes the following components by weight: 5–23 parts of rice husk ash and 3–13 parts of carbide slag.

2. A red clay modifier according to claim 1, characterized in that: The invention comprises the following components by weight: 5 parts of rice husk ash and 3 parts of carbide slag.

3. A red clay modifier according to claim 1, characterized in that: The invention comprises the following components by weight: 10 parts of rice husk ash and 6 parts of carbide slag.

4. A red clay modifier according to claim 1, characterized in that: The invention comprises the following components by weight: 16 parts of rice husk ash and 9 parts of carbide slag.

5. A red clay modifier according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 23 parts of rice husk ash and 13 parts of carbide slag.

6. A method for improving a red clay modifier according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1: Mix different amounts of rice husk ash and carbide slag with red clay according to the optimal ratio of 65:35 to obtain improved soils of different amounts; Step 2: Obtain the maximum dry density and optimum moisture content of the improved soil at each dosage after mixing; Step 3: preparing various test specimens of each improved soil according to the maximum dry density and the optimum moisture content and curing them for 28 days; Step 4: Conduct relevant mechanical property tests on each of the test specimens; Step 5: According to the mechanical properties test results, determine the optimal dosage of rice husk ash and carbide slag to improve red clay.

7. The method for improving a red clay modifier according to claim 6, characterized in that: Before the step 1, the method further comprises crushing the red clay, wherein the red clay is crushed to a particle size of less than 2 mm.

8. The method for improving a red clay modifier according to claim 6, characterized in that: In the step 2, obtaining the maximum dry density and the optimum moisture content of the improved soil at each dosage after mixing includes: Divide the mixed materials of each dosage obtained by mixing into a plurality of samples; Each dosage should be mixed with water according to at least 5 moisture contents; The mixed samples were placed in plastic bags and sealed for 12 hours; the sealed samples were placed in a compaction cylinder and compacted; Use a bulldozer to push out the sample in the cylinder, and take a representative soil sample from the center of the sample to measure its moisture content; Draw the relationship curve between dry density and moisture content and obtain the maximum dry density and optimal moisture content of the sample.

9. The method for improving a red clay modifier according to claim 6, characterized in that: In the step 3, the test specimen is prepared by a heavy test method and a small cylinder three-layer method; during the preparation process, each layer is about 800-900g, and after the small test cylinder is compacted, the sample should not be higher than 5mm from the top surface of the cylinder; the heavy test method is used and the preparation is carried out according to the small cylinder three-layer method, which specifically includes: Each dosage should be mixed with water according to at least 5 moisture contents; each mixed sample should be placed in a plastic bag and sealed for 12 hours; each sealed sample should be placed in a small test tube and compacted; and the sample in the tube should be pushed out with a bulldozer.

10. The method for improving a red clay modifier according to claim 6, characterized in that: In the step 4, the relevant mechanical property tests include: unconfined compressive strength, shear strength index and compression performance; the shear strength index is a triaxial test without consolidation and drainage; the unconfined compressive strength test specimens and the unconsolidated undrained triaxial test specimens are made by compaction method, and the specimen size is 39.1 mm in diameter × 80 mm in height, and is cured for 28 days under standard curing conditions and a temperature of 20-22°C and a relative humidity of more than 95%.

Citation Information

Cited By

  • Sludge solidified body circulating hydration method based on excitation of rice hull ash activity by carbide slag

    CN120622759A